Dysphagia as presenting symptom of myasthenia gravis: a case series of successful outcome in multidisciplinary approach - Anton Haryono; Rery Budiarti; . Muyassaroh (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Dysphagia can be caused by mechanic or neurologic disorders. Neurologic dysphagia is commonly related to cerebrovascular disease, parkinson disease, amyotropic lateral sclerosis, tardive dyskinesia, and myasthenia gravis (MG). About 15-40% dysphagia occurred in MG generalized type. Only 6% MG with dysphagia were reported as a single symptom. The case reports aimed to demonstrate the role of otolaryngologist in multidisciplinary approach of the MG management. Two cases of MG were reported. First case was a 33 years old woman with moderate MG generalized type with ocular, dysphagia, and disarthria symptoms and second case was a 46 years old man with acute severe MG with crisis. Management therapy was applied according to onset and severity of MG. Acetylcholinesterase (AChE) and corticosteroid were administered for the first case, whereas therapeutic plasma exchange (TPE) for second case. In conclusion, disfagia in MG can be accompanied with other symptom, therefore its management should be based on the severity in order to give a positive result.